Effects of cadmium on the anatomical structures of vegetative organs of chickpea (Cicer arientinum L.) - Liza, Saima Jahan; Shethi, Kishwar Jahan; Rashid, Parveen (Dhaka University Journal of Biological Sciences, 2020)
The effects of cadmium on the anatomical structures of different vegetative parts, namely root, stem and leaf of chickpea, Cicer arientinum L. was studied. Four different concentrations of CdCl2 e.g. 250, 500, 750 and 1000 μM were considered as treatments alongside non treated samples (control). In case of root anatomy decrease of root diameter, root cortex area, thick walled endodermal layer and reduced number of metaxylem vessels were observed compared to control. Similarly, stem diameter, cortical area, size and number of xylem vessels were decreased in Cd treated stem. However, large and increased number of trichomes had been found in Cd treated stem samples with deposition of phenolic compounds in vessels with increasing concentration of Cd. Considerable less toxic effects were observed in leaf anatomy except decrease in leaf thickness, reduced vascular area and closure of stomata in comparison to control sample. All such plant anatomical alterations indicated adverse effects as well as tolerance of chickpea up to certain concentrations of heavy metal to cope up with the changing environment. Dhaka Univ. J. Biol. Sci. 29(1): 45-52, 2020 (January)